Sagot :
The answer is 900.
──────────────────────
Parenthesis , first () , then [] , then {}
Exponential
Multiplication (from left to right)
Division (from left to right)
Addition (from left to right)
Subtraction (from left to right)
──────────────────────
➣ Solution:
- [tex]\orange{\tt{\{ 10 + [ 4 ⋅ 3 - 2 + ( 27 : 3 + 1)]\}^2 =}}[/tex]
- [tex]\orange{\tt{\{ 10 + [ 4 ⋅ 3 - 2 + ( 9 + 1) ] \}^2 = }}[/tex]
- [tex]\orange{\tt{\{ 10 + [ 4 ⋅ 3 - 2 + ( 10)]\}^2=}} [/tex]
- [tex]\orange{\tt{\{ 10 + [ 4 ⋅ 3 - 2 + 10]\}^2=}}[/tex]
- [tex]\orange{\tt{\{ 10 + [12 - 2 + 10]\}^2=}}[/tex]
- [tex]\orange{\tt{\{ 10 + [10 + 10]\}^2=}}[/tex]
- [tex]\orange{\tt{\{ 10 + [20]\}^2=}}[/tex]
- [tex]\orange{\tt{\{ 10 + 20\}^2=}}[/tex]
- [tex]\orange{\tt{\{ 30\}^2=}}[/tex]
- [tex]\orange{\tt{\{ 900 \}=}}[/tex]
- [tex]\underline{\boxed{\tt{\orange{\: \:900\: \:}}}}[/tex]
Solution
(10+(4×3-2+(27÷3+1)²
(10+(4)(3)-2+27÷3+1)²
=(10+12-2+27÷3+1)²
=(10+10+27÷3+1)²
=(10+10+9+1)²
=(10+10+10)²
=(10+20)²
=30²
=900